(تحضير تركيبة من مستخلصات نباتية لمكافحة الحشرات الماصة الثاقبة (صديقة للبيئة - عباس هوازن عبدلله; جواد اسيل طارق; صالح هنـد وليد; فريح سهام; خلف محمد زيدان; سلمان عدنان حافظ; حسن باسم حسون; مصلح عمر عبد الرزاق (Al-Nahrain Journal of Science, 2018)
Abstract: The conventional pesticides (chemical) have an adverse effect on the environment and human health, which led to find alternatives to those chemical pesticides that has an effective impact against sucking insects insightful (such as aphids)., And those insects infect plants eaten by humans causing economic loss with expensive crops. Research is designed to prepare pesticide plant safe and non-toxic (pesticide naturally) insecticide (environmentally friendly). The pesticide were prepared of natural plant extract mixed with corn oil and Rosemary oil (Rosemary Oil) with certain volumetric proportions then it was measured by its impact on green peach trees (peach aphid MyzsePersicae) in orchards in central Iraq precisely the spring season of 2011, testing the level of peach trees aged 6-8 years and the results indicate that the pesticide record gave a clear impact on the aphids. Where it decreased the average number of total insects to (204) after 24 hours of treatment and then dropped to (32) after 48 hours of treatment and fell to (6) after 72 hours in a row, the time within which noticing the large increase of the total insect prepared within control treatment recording (841) after 24 hours while reached (1188) after 72 hours. The results show the effective influence of the prepared pesticide and is considered an alternative to carcinogenic chemicals, it can be used with in programs to control operations to eliminate aphids.